Preexisting melanoma and hematological malignancies, prognosis, and timing to solid organ transplantation: A consensus expert opinion statement. Issue 2 (10th October 2020) - Al‐Adra, David P.; Hammel, Laura; Roberts, John; Woodle, E. Steve; Levine, Deborah; Mandelbrot, Didier; Verna, Elizabeth; Locke, Jayme; D'Cunha, Jonathan; Farr, Maryjane; Sawinski, Deirdre; Agarwal, Piyush K.; et al.
Abstract : Patients undergoing evaluation for solid organ transplantation (SOT) frequently have a history of malignancy. Only patients with treated cancer are considered for SOT but the benefits of transplantation need to be balanced against the risk of tumor recurrence, taking into consideration the potential effects of immunosuppression. Prior guidelines on timing to transplant in patients with a prior treated malignancy do not account for current staging, disease biology, or advances in cancer treatments. To update these recommendations, the American Society of Transplantation (AST) facilitated a consensus workshop to comprehensively review contemporary literature regarding cancer therapies, cancer stage specific prognosis, the kinetics of cancer recurrence, as well as the limited data on the effects of immunosuppression on cancer‐specific outcomes. This document contains prognosis, treatment, and transplant recommendations for melanoma and hematological malignancies. Given the limited data regarding the risk of cancer recurrence in transplant recipients, the goal of the AST‐sponsored conference and the consensus documents produced are to provide expert opinion recommendations that help in the evaluation of patients with a history of a pretransplant malignancy for transplant candidacy. Abstract : This article presents consensus expert opinion recommendations regarding the timing of transplantation for patients with a history of melanoma or hematological malignancies. The companion review is on page 460 and an editorial from Hart and Engels is on page 447 .